Maternal perception Regarding Nursing care during labor - Rashid, Sara Ahmed; Ameen, Wafaa Ahmed (Journal of Neonatal Surgery, 2025)
Background: The quality of intrapartum care, as well as the attitudes and behavior of the midwives assisting the birth, can significantly affect maternal perception of nursing care and support during childbirth. This perception can have a long-term positive or negative impact, influencing future expectations of childbirth and ensuring the best possible outcomes. Objectives: This study aimed to assess maternal perceptions regarding nursing care during labor among postnatal women, to determine the relationship between maternal perception and socio-demographic variables, and to determine the relationship between maternal perception and obstetric history of postnatal women regarding nursing care during labor. Methods and Material: A descriptive study was conducted in Bent Al-Huda and Al-Haboubi Teaching Hospitals in Al-Nasiriya city from October 1, 2023, to March 15, 2025. Statistical Analysis: Data were collected using a questionnaire. The collected data were tabulated and analyzed using descriptive and inferential statistical approaches with Microsoft Excel (2016) and the Statistical Package for the Social Sciences (SPSS) version 26.0. Results: The average age of the women was 20-24 years. Among the participants, 25.7% had completed primary school, 47.9% were first-time mothers, 25.7% had four or more pregnancies (gravida), 81.3% had never experienced an abortion, 97.1% had delivered vaginally in previous pregnancies, and 81.9% chose private clinics for their prenatal visits. The majority (83.5%) of mothers had a high perception of nursing care during labor. Conclusions: The overall assessment of mothers' perceptions regarding nursing care during labor was high. Significant positive correlations were observed between overall perception and socio-demographic variables, while no significant relationship was found between maternal perception and obstetric history. Recommendations include continuous development programs for nursing staff, focusing on labor and delivery care. Future studies should be conducted on other nursing care situations to assist mothers in describing their feelings towards healthcare during labor..